2021
DOI: 10.28983/asj.y2021i6pp21-26
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weather and climatic conditions on the phenological indicators and productivity of winter wheat cultivated by direct seeding technology in the arid zone of the Stavropol Territory

Abstract: The studies were conducted in the arid zone of Stavropol region to determine the productivity of winter wheat cultivated by direct seeding technology, based on phenological observations and NDVI. The work was carried out on the basis of the agro-enterprise JSC "Agrohleboprodukt" for 2018-2020. The predecessors are sunflower, chickpeas, winter wheat varieties (Zustrich (St.), Bagheera and Bagrat). Plant samples were selected according to the generally accepted method. Satellite mapping data of vegetation cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…A slight increase in the average annual HTC (up to 0.43 in 2021) transforms the relationship between humidity and duration of interphase periods of plant development-the effect is observed in the sprouting phase (0.03 after sunflowers and 0.04 after chickpeas). This finding correlates with the results of the earlier studies of Dridiger and Gadzhiumarov [62] and Pismennaya et al [20], who demonstrated that in extremely arid areas, precipitation in winter and during the growing season increases winter wheat yields significantly, especially after sunflower.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A slight increase in the average annual HTC (up to 0.43 in 2021) transforms the relationship between humidity and duration of interphase periods of plant development-the effect is observed in the sprouting phase (0.03 after sunflowers and 0.04 after chickpeas). This finding correlates with the results of the earlier studies of Dridiger and Gadzhiumarov [62] and Pismennaya et al [20], who demonstrated that in extremely arid areas, precipitation in winter and during the growing season increases winter wheat yields significantly, especially after sunflower.…”
Section: Discussionsupporting
confidence: 92%
“…Supporting the findings of Szczepanek et al [28] and Hou et al [93], who revealed a significant correlation of the grain yield with the amount of precipitation in tillering, the study concludes that drought affects the duration of interphase periods of winter wheat development mainly in the phases of spring tillering and earing (in 2019, HTC = 0.85) (Table 8). Earlier, Pismennaya et al [20] found that at the tillering stage, the coefficient of variation showed no substantial heterogeneity of the phenological index for winter wheat. Conversely, this study demonstrates that the proximity of D index in different phases of plant development indicates homogeneity of phenotypic processes.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations